Knee osteoarthritis radiographic progression and associations with pain and function prior to knee arthroplasty: a multicenter comparative cohort study. Issue 3 (March 2015) - Riddle, D.L.; Jiranek, W.A.
Summary: Objectives: We determined the radiographic osteoarthritic worsening rate prior to knee arthroplasty (TKA) and whether this worsening was associated with worsening pain and function as compared to a non-surgical matched sample. Methods: We used the Osteoarthritis Initiative 5-year datasets. Extent of knee OA 2 years prior to total knee arthroplasty (TKA) was matched to knees of persons who did not undergo TKA. Western Ontario and McMaster Universities Arthritis Index (WOMAC) Function and Knee injury and Osteoarthritis Outcome Score (KOOS) Pain scales were used to quantify functional deficit and functionally relevant pain respectively. A total of 167 persons with isolated TKA and 300 persons with matched symptomatic knee OA but no TKA were studied. Results: During the 2 years prior to TKA, worsening by at least one Kellgren and Lawrence (KL) grade occurred in 27.4% (95% CI = 20.6–34.2) of the surgical knees compared to 6.6% (95% CI = 3.8–9.4) of matched non-surgical knees. Osteoarthritis radiographic progression was strongly associated with WOMAC Function and KOOS Pain worsening ( P  < 0.001) in the 2 years prior to TKA. KL worsening was strongly associated with future arthroplasty (Odds ratio = 5.0, 95% CI = 2.6–9.8) after adjustment for potential confounders. Conclusions: Persons undergoing TKA 2 years later had substantial worsening pain and function over the 2-year pre-operative period as compared to a non-surgical sample matched based on KL grades. Almost 30% of persons who elect to undergo TKA undergo rapid disease progression and symptom worsening during the 2 years prior to TKA.